PENGARUH FINANCIAL DISTRESS, AUDIT COMPLEXITY, DAN KOMPLEKSITAS OPERASI TERHADAP AUDIT DELAY - Tanya Karina, (2022)
This study was conducted with the aim of testing the effect of financial distress, audit complexity, and operating complexity on audit delay in miscellaneous industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 observation period. The sample selection technique used was purposive sampling which resulted in 37 companies with a total sample of 111 in according with the criteria. This qualitative research by utilizing data on financial statements. Logistic regression and using SPSS software version 26 for hypothesis testing. The results of this study indicate that financial distress has a negative effect on audit delay, audit complexity does not affect audit delay, and operational complexity does not affect audit delay.